The Effects of Carbon Monoxide Treatment on the Physical and Chemical Qualities of Tuna Steak during Iced Storage - Farida Ariyani; Ellia Kristiningrum; Giri Rohmad Barokah; Hedi Indra Januar (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2020)
Injection or modification of the atmosphere in the meat packaging by carbon monoxide (CO) has been known to retain the color stability of red meat including those of tuna. The red color in tuna meat has been commonly used as a freshness indicator by consumers, especially those for raw consumption. However, other information on the freshness level in fish, in addition to color, is also important to assess in the food safety of marine and fisheries products. This study aims to evaluate the effects of CO on the chemical and physical properties of tuna steak during storage on ice. This study was conducted using bigeye tuna (Thunnus obesus) as the raw material. The tuna was cut into loins to form steaks and divided into two groups, one group without CO injection or control, and another group was injected with CO. Both CO-treated tuna steak and control were preserved in a cool-box filled with ice for 14 days. The observation was conducted every two days by determining color (chromameter method), sensory preference (hedonic method), and several chemical parameters, including total volatile base (TVB), K value, and histamine content that related to the spoilage process. Results showed that after 14 days of preservation in iced storage, the reddish color of CO-treated tuna steak was retained, whereas that of control turned brown. In the sensory tests, the panelists preferred the CO-treated tuna steak to control due to its reddish color. There were no significant differences between the content of TVB accumulation and the K value in CO-treated tuna steak and the control. Furthermore, the K value of CO-treated tuna steak and control reached the rejected level on day 14. The difference between CO-treated tuna steak and control was based on the content of histamine, where that of control was significantly higher than tuna steak treated with CO. Therefore, this research showed that the effects of CO treatment were only on the appearance of the steak; meanwhile, the deterioration process in fish is generally unaffected. Precautions are thus needed for consumers, since color may not be the only factor that indicates the freshness of tuna steak.